KEBIJAKAN PENILAIAN PRESTASI KERJA PEGAWAI NEGERI BERDASARKAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2011 - Alex Sugara; Sujianto Sujianto; Muchid Muchid (Universitas Riau, 2018)
Civil Servant Performance Assessment Policy Based on Government RegulationNumber 46. Year 2011. The purpose of this study was to determine and analyze the workperformance appraisal of civil servants based on Government Regulation No. 46 of 2011 at theRegional Office XII of the Pekanbaru Civil Service Agency. This research was carried out with aqualitative approach, where the informants in this study were work performance appraisers andapparatuses who assessed their work performance. Data collection was done by observation andinterview, where after the data was collected then analyzed with qualitative descriptive method.The results of this study found that the employee performance appraisal based on GovernmentRegulation Number 46 of 2011 at the Regional Office XII Pekanbaru State Personnel Agency hasrun quite well, where in the process of work performance appraisal, the Regional Office XIIPekanbaru Civil Service Agency has followed the regulation. While the factors that inhibit theassessment of employee performance are centeral tendency factors and recency effect factors.